Managing loneliness: a qualitative study of older people's views. (3rd July 2021) - Kharicha, K.; Manthorpe, J.; Iliffe, S.; Chew-Graham, C. A.; Cattan, M.; Goodman, C.; Kirby-Barr, M.; Whitehouse, J. H.; Walters, K.
Abstract: Engaging with older people who self-identify as lonely may help professionals in mental health and other services understand how they deal with loneliness. The evidence-base for effective interventions to address loneliness is inconclusive. This study aimed to explore how community-dwelling lonely older people in England manage their experiences of loneliness. Twenty eight community-dwelling older people identifying as lonely, based on responses to two loneliness measures (self-report and a standardised instrument), participated in in-depth interviews between 2013 and 2014. Fifteen lived alone. Thematic analysis of transcribed interviews was conducted by a multidisciplinary team including older people. Participants drew on a range of strategies to ameliorate their distress which had been developed over their lives and shaped according to individual coping styles and contexts. Strategies included physical engagement with the world beyond their home, using technologies, planning, and engagement with purpose in an 'outside world', and acceptance, endurance, revealing and hiding, positive attitude and motivation, and distraction within an 'inside world'. Strategies of interests and hobbies, comparative thinking, religion and spirituality and use of alcohol straddled both the inside and outside worlds. Participants conveyed a personal responsibility for managing feelings of loneliness rather than relying on others. This study includes the experiences of those living with loneliness whilst also living with other people. When developing policy and practice responses to loneliness it is important to listen attentively to the views of those who may not be engaging with services designed for 'the lonely' and to consider their own strategies for managing it.